MUSIC VIDEO “SIRNA” AS A PROMOTIONAL MEDIA FOR THE FLINT BAND - Ekaputra, Dimas Ariasmara; Pratiwinindya, Ratih Ayu (LPPM Univ. Ibn Khaldun Bogor, 2025)
Music videos have evolved into an essential medium for building visual identity and promotional strategy for musicians, especially in today’s highly competitive digital era. This article discusses the design process of the Sirna music video as a promotional medium for FLINT, an independent artpop band from Jakarta. The main problem faced by FLINT is the lack of representative visual promotional media, which hampers the delivery of their artistic image to the audience. In this study, the production process was carried out through three stages: pre-production, production, and post-production. The focus is placed on the application of cinematographic strategies and visual storytelling to create a visual narrative that aligns with the emotional tone of the song. The result is a 4-minute-47-second video that combines monochromatic aesthetics, expressive dance movements, motion blur effects, and visual symbolism to represent the theme of loss. This work demonstrates that music videos can serve as an effective medium to strengthen brand image, build emotional engagement with audiences, and enhance the visibility of independent musicians through digital distribution.